Growth kinetic of Pleurotus-Sajor-Caju mycelium from multiple subculture by using tissue culture technique - Awang Abdul Rahman Awang Bujang (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
This study was conducted to evaluate the effect of P.sajor-caju mycelium growth of multiple subculture. P.sajor-caju is the favorite food of Asia, this is due to the appearance of it in the form of oysters. Additionally, P.sajor-caju has a delicious flavor, and this makes it as a favorite food. P.sajor-caju also believed to have a high nutritional value especially protein. Protein in it is said to be superior to the value of protein in meat and fish and two times more than the value of the protein in the vegetables. Additionally, P.sajor-caju reliable supplier of vitamin B, riboflavin, niacin and panthothenic acid used for break down the proteins, fats and carbohydrates. The market demand of P.sajor-caju in Malaysia is higher than production of it, this require the P.sajor-caju to be imported from the other countries. These studies are used to increase production P.sajor-caju in Malaysia, to be able to reduce the budget. To increase the production of P.sajor-caju various studies have been done, one of the study is to investigate the effects P.sajor-caju mycelium growth rate on multiple subculture. In this study, there are different rates of growth after multiple subculture, this study was able to increase the growth rate P.sajor-caju by identifying the growth factors.